Évacuation massive des populations en temps d’épidémie de COVID-19 : comment éviter la sur-crise ? - Éric Daudé; Delphine Grancher; Franck Lavigne (EchoGéo)
This paper offers a reflection on the constraints imposed by the focus of the management of the pandemic at the global level and of the epidemic at the level of the territories on the preparation and anticipation of new threats, such as natural hazards.